Advancements in insulin delivery: the potential of natural polymers for improved diabetes management - Ghazwani, Mohammed; Hani, Umme; Kyada, Ashishkumar; Ballal, Suhas; Issa, Bahjat Saeed; Abosaoda, Munthar Kadhim; Singh, Abhayveer; Sabarivani, A.; Ray, Subhashree (Frontiers in Bioengineering and Biotechnology, 2025)
Diabetes is a growing global health issue, with millions of people affected by the condition. While insulin therapy is vital for managing both Type 1 and Type 2 diabetes, traditional methods such as subcutaneous injections have notable drawbacks, including pain, discomfort, and difficulty in maintaining stable blood sugar levels. To improve insulin delivery, research is increasingly focused on the use of natural polymers—substances derived from plants, animals, and microorganisms. These polymers, including materials like alginate, chitosan, and hyaluronic acid, have promising properties such as biocompatibility, biodegradability, and the ability to provide controlled, sustained insulin release. By encapsulating insulin in polymers, it is protected from degradation and released in a manner that more closely mirrors the body’s natural insulin production. Furthermore, the development of non-invasive delivery methods, such as oral and transdermal systems, is gaining momentum, offering the potential for more patient-friendly treatment options. This review discusses the role of natural polymers in insulin delivery, examining their mechanisms, types, and current research efforts. It also addresses the challenges that remain in advancing these technologies into practical clinical use, aiming to provide more efficient, comfortable, and effective solutions for diabetes management.